Productivity changes for trawlers and purse seiner in two regions and fishing zones in Peninsular Malaysia - Syed Seman, Sharifah Erin (2012)
Marine fish landings in Peninsular Malaysia have shown increasing pattern starting from year 1996 to 2009. Most of the total landings in Peninsular Malaysia had come from inshore fisheries. The objective of this study is to examine technical efficiency and productivity fishing gear (trawl and purse seines) in different region and fishing zone. Data for the study was collected from Malaysia Fisheries Department between 2000 until 2009. Information on number of fishing units, number of days, number of trips, number of hauls and number of hours were gathered and analysed using the Data Envelopment Analysis (DEA) and Malmquist Index. Results of the study shows that, most of purse seines operating in the frontier line in inshore location while majority of trawl net operating below the frontier line for both fishing zone. Overall, technical efficiency of trawl in Peninsular Malaysia is 26% and 100% for purse seines. This implies inputs were not used efficiently and systematically by trawl net. Inputs used in this study are, number of fishing gear, number of days, number of trips, number of hauls and number of hours. Total Factor Productivity (TFP) for trawl increased in west coast for both sea locations and decreased in east coast for both sea locations. Meanwhile Total Factor Productivity for purse seines increased in east coast for both sea locations and decreased in west coast for both sea locations. Overall, Total Factor Productivity for trawl in Peninsular Malaysia is 23.4% and 28.7% for purse seines. These findings suggest that there is much room for improvement for trawl and purse seines in deepsea and inshore in term of technical efficiency and productivity with appropriate training, regular monitoring and usage of more advanced technologies. In conclusion the analyzed period of time we found that the increased in marine fish catches in line with the increased use of technology to suit the zone location.